Random Walk Conformer: Learning Graph Representation from Long and Short Range - Yeh, Pei-Kai; Chen, Hsi-Wen; Chen, Ming-Syan (Proceedings of the AAAI Conference on Artificial Intelligence, 2023)
While graph neural networks (GNNs) have achieved notable success in various graph mining tasks, conventional GNNs only model the pairwise correlation in 1-hop neighbors without considering the long-term relations and the high-order patterns, thus limiting their performances. Recently, several works have addressed these issues by exploring the motif, i.e., frequent subgraphs. However, these methods usually require an unacceptable computational time to enumerate all possible combinations of motifs. In this paper, we introduce a new GNN framework, namely Random Walk Conformer (RWC), to exploit global correlations and local patterns based on the random walk, which is a promising method to discover the graph structure. Besides, we propose random walk encoding to help RWC capture topological information, which is proven more expressive than conventional spatial encoding. Extensive experiment results manifest that RWC achieves state-of-the-art performance on graph classification and regression tasks. The source code of RWC is available at https://github.com/b05901024/RandomWalkConformer.